Policy Note on Belarus Hospital Optimization - World Bank (World Bank, Washington, DC, 2021)
Though Belarus has achieved improvements in key health outcomes, it faces a growing burden of noncommunicable diseases (NCDs). Demographic processes in the Republic of Belarus are accompanied by a high rate of NCDs, with cardiovascular diseases (CVDs) being a leading cause of mortality and morbidity in the country. The objective of the Advisory Services and Analytics (ASA) was to help the government in developing an understanding of the vision on hospital optimization for 2021–2025, considering lessons learned from other Europe and Central Asian countries. The paper starts with Chapter 1, defining the epidemiological profile of Belarus, its burden of diseases, organization of hospital service delivery, and utilization of these services in a manner that sets the stage for the subsequent discussion; Chapter 2 on the explanation of the health financing mechanism in the country and provides information on imbalances in the financing of the health system in Belarus, referring to the Belarus Health Public Expenditure Review (2018); Chapter 3 of the paper describes the government proposal on the creation of the interregional centers (IRCs) and interdistrict centers (IDCs) and how these centers fit into the health care delivery system and their role and functionality; Chapter 4 shares international practice, to understand how countries such as Estonia, Finland, Denmark, Germany, Netherlands, and Australia are dealing with similar health care issues and how their health care services are organized to address cardiovascular morbidity and mortality; and Chapter 5 proposes some potential options for changes in the organization and delivery of hospital services, based on the discussions and issues raised in the previous chapters as well as on the analysis of hospitals in the two regions of Brest and Gomel.